Political history and disparities in safe motherhood between Guatemala and Honduras - Shiffman, J.; Garces del Valle, A. L.
il.
pp. 53-80
Keywords: Honduras; Guatemala; Historia Politica; Maternidad; Mujeres; Mortalidad